Micronutrients absorbed via the oral mucosa reduce emotion dysregulation in 5-10-year-old children: A three-phased randomized wait-list-controlled trial. - Nurina M Katta; Neville M Blampied; Matt Eggleston; Julia J Rucklidge (PLoS ONE)
Objective Previous evidence has established that micronutrient capsules can improve emotion regulation in children. This three-phased randomized open-label waitlist-controlled study investigated the safety of a micronutrient powder absorbed by the oral mucosa and its effects on emotion dysregulation in 5-to-10-year-old children. The primary outcome measures were the Revised Clinician-rated Temper and Irritability Scale (CL-ARI) and the Clinical Global Impressions-Improvement Scale (CGI-I). Method Forty-eight children with moderate-to-severe symptoms of irritability were randomized to an initial treatment group (ITG) or waitlist control group (IWLG) (four-week delayed start), followed by the two groups alternating between taking the micronutrients for four weeks or having a four-week break. For the last three months of the trial, both groups took the micronutrients continuously. Results Overall adherence rates were high (93%). At the end of RCT phase, there were large group differences (CL-ARI; d = 1.25, p < .001), and 67% in the ITG and 8% in the IWLG were 'much' or 'very much' improved (CGI-I). Further, the ITG displayed a clinically meaningful reduction in Attention Deficit/Hyperactivity Impulsivity Disorder (ADHD) and Oppositional Defiant Disorder (ODD) symptoms as measured with the Child Swanson, Nolan, and Pelham-IV Questionnaire 26 (SNAP-IV) compared to IWLG. The treatment effect regressed when participants stopped taking the micronutrients and was reinstated when participants were taking the micronutrients. The observed benefits were maintained over a sustained time period. The IWLG reported significantly more headaches (p = .040) and sweating (p = .037) at the end of RCT. By the end of the study, seven participants (14.5%) dropped out non-differentially by group (p = .22). Conclusion The findings showed that micronutrients absorbed by the oral mucosa are a safe intervention that can effectively improve emotion dysregulation in children. Future double-blinded, randomized, placebo-controlled trials are needed to support these findings.